A Cross-National Look at Married Women's Economic Dependency - Suzanne M. Bianchi; Lynne M. Casper; Pia K. Peltola (Luxembourg Income Study (LIS), 1996)
Using the LIS data, the authors examine married women's dependency on their husbands' earnings in nine Western industrialized countries: Australia; Belgium; Canada; Finland; Germany; Netherlands; Norway; Sweden; and the United States. When we examine the level and degree of dependency, and the labor force participation of married women, the nine countries cluster in three groups along the lines of the Esping-Anderson welfare state typology. But when we examine the determinants of the dependency within each country, the clustering disappears. Wives' dependency increases with age, the presence of young children, and the number of children. It is reduced when wives' labor force participation and education are high relative to their husbands and in families which rely more on unearned sources of income. The similarity of patterns across countries suggests that gender differences in the work-family nexus are deeply entrenched in all countries and continue even in the face of very active social policy to minimize their effects.
Keywords: 330; Weibliche Arbeitskräfte; Mütter; Familie; Industrieländer